Understanding Entrepreneurial Intention Among Person with Disabilities: A Conceptual Review of Psychological, Social, and Structural Determinants. International - Zulqernain, Nurul Syaqirah; Mohd Firdaus Kozako, Intan Nurul’Ain; Nik Hassan, Nik Suriati; Zahid, Putra Faizurrahman; Mohd Pauzi, Nooradzlina (International Journal of Accounting, Finance and Business, 2025)
Entrepreneurship offers persons with disabilities (PwDs) an important pathway to overcome employment barriers and achieve social inclusion. Although research on entrepreneurial intention has grown, studies focusing on PwDs remain fragmented, often examining either psychological, social, or structural factors in isolation. This paper develops a conceptual framework based on the Theory of Planned Behavior (TPB) that integrates psychological elements such as motivation and self-efficacy, social aspects including family support and societal attitudes, and structural factors such as financial access and inclusive policies. Using a narrative synthesis of peer-reviewed studies published between 2015 until 2024, the paper identifies key themes, contradictions, and gaps in existing scholarship. Its novelty lies in offering a holistic perspective that explains entrepreneurial intention among PwDs as the outcome of intersecting individual capacities and enabling environments. The framework provides a stronger theoretical foundation to guide future empirical studies while offering practical insights for policymakers, educators, and support organizations seeking to promote inclusive entrepreneurship.